Pengabdian Masyarakat di Masa Pandemi Covid-19 Pada Prodi Teologi Hindu di STAHN Mpu Kuturan Singaraja - Ni Made Yunitha Asri Diantary; I Wayan Titra Gunawijaya; I Ketut Wartayasa (Jayapangus Press, 2021)
This community service is a type of non-formal education that is able to educate people to like learning (learning society) regardless of age, community service carried out by the Hindu Theology study program which is in the realm of religion is very relevant to religious activities in Bali so as to be able to provide assistance. community expertise in problem solving. The Hindu Theology Study Program has scholars, experts, and students who can be utilized optimally by the community for the sake of creating harmony between fellow humans, humans and the natural environment, and a harmonious relationship with God Almighty, as in accordance with the teachings of Hinduism in the concept of Tri Hita Karana. So that the implementation of community service is important as an improvement in the quality of the institution and also the welfare of the community. This form of service implementation follows the service guidelines that have been set by STAHN Mpu Kuturan Singaraja by providing education, services and including students in every community activity. The noble purpose of community service is of course to create quality human resources and produce outputs that have a contribution to the wider community and universities.